One-Rupee Ultrasensitive Wearable Flexible Low-Pressure Sensor - Bijender (ACS Omega, 2020)
[Image: see text] A capacitive flexible pressure sensor with polydimethylsiloxane (PDMS) as an elastomeric dielectric layer sandwiched between two flexible conducting electrodes is developed. The porosity/flexibility of PDMS has been increased by altering its microstructure by incorporating a thin layer of a scrubber into the dielectric layer to improve the pressure sensitivity. The fabricated sensor with a porous PDMS–scrubber composite (microstructured/porous PDMS layer) shows 0.058–25.84% relative capacitance change with varying static pressure from 4.4 Pa to 216 kPa. The sensor device with a porous PDMS layer showed a significantly high sensitivity (%) of 0.0083 Pa(–1) in a low-pressure range (less than 0.022 kPa) and has a fast response, long-life, and ultralow pressure detection limit. The sensitivity associated with the device was found to vary with the effective area of the device. The pressure sensitivity associated with devices having an effective area of 324 mm(2) was 10 times more than that of the sensor having an effective area of 36 mm(2). Due to the high sensitivity of the sensor in a wide pressure range, low manufacturing cost, and simple and convenient way of fabrication, this flexible pressure sensor shows potential for pressure and wearable applications.